PROTOTYPE MONITORING KETINGGIAN AIR SUNGAI MENGGUNAKAN TELEGRAM - Muhammad Fahrurrozi; Safarwadi Safarwadi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2024)
The rainy season is the main cause of fear, especially for residents of Dusun Keang, Santong Village, East Lombok Regency, West Nusa Tenggara. The reason is, every rainy season there are definitely several areas that are flooded. The main cause of this condition is due to the increase in water volume in the Dusun Keang river, causing the river water level to increase and eventually overflow into residential areas. The Keang River is one of the rivers that is a source of water that has an important role for the community, such as a source of water for agriculture, and to support daily activities for the community. The depth of the Keang River reaches 3 meters, and especially during the rainy season the water level of the Keang River often experiences significant changes, even causing flooding. In this case, to prevent flooding, a special tool is needed to monitor changes in water discharge in the river at all times in real time. One of them is by using a tool called the River Water Level. River Water Level is a tool that can be used to monitor changes in water discharge in rivers. The river water level monitoring tool can provide information on river water levels automatically through the Telegram application in real time so that it can anticipate and prevent the impacts caused by flooding. From 20 trials, a success rate of 100% was obtained.